(3TQM NhU GdNGJe GdeHGQcs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3gPG efHYV NhJGU gPG GdNGJe GdeHGQc GdeSeG HGdNGJe GdgGQhfi s
(3Vef eLehY , JQJjHgG (B: (3GdKGdKs
(3hQO GYfhGf GdCUdi ajX HQbe (B698/1s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMQha h GdChaGbs